Revised American Thyroid Association guidelines for the management of medullary thyroid carcinoma: the American Thyroid Association guidelines Task Force on medullary thyroid carcinoma - Wells, Samuel A.; Asa, Sylvia L.; Dralle, Henning; Elisei, Rossella; Evans, Douglas B.; Gagel, Robert F.; Lee, Nancy; Machens, Andreas; Moley, Jeffrey F.; Pacini, Furio; Raue, Friedhelm; Frank-Raue, Karin; et al. (Thyroid, 2015)
Introduction:The American Thyroid Association appointed a Task Force of experts to revise the originalMedullary Thyroid Carcinoma: Management Guidelines of the American Thyroid Association.Methods:The Task Force identified relevant articles using a systematic PubMed search, supplemented withadditional published materials, and then created evidence-based recommendations, which were set in categoriesusing criteria adapted from the United States Preventive Services Task Force Agency for Healthcare Researchand Quality. The original guidelines provided abundant source material and an excellent organizationalstructure that served as the basis for the current revised document.Results:The revised guidelines are focused primarily on the diagnosis and treatment of patients with sporadicmedullary thyroid carcinoma (MTC) and hereditary MTC.Conclusions:The Task Force developed 67 evidence-based recommendations to assist clinicians in the care ofpatients with MTC. The Task Force considers the recommendations to represent current, rational, and optimal medical practice.